Society perceptions between conventional and islamic life insurance: A case study in Bandar Jengka Pahang / Irzan Ismail - Ismail, Irzan (2004)
Human beings are not far different from other living thing as we are exposed to various risks. In our daily life, uncertainties always exist. This is one of the reasons that limit our capability. To most people, risk implies some form of uncertainty about an outcome in given situation. Having a life insurance is one form of risk transfer mechanism that would offer numerous benefits against these uncertainties. As a social and economic device, life insurance is a method by which a group of people may cooperate to ameliorate the loss resulting especially due to premature death. It is very important for us to realize that life insurance is more than just a financial agreement or financial protection but it has become a need in this challenging environment where it offers different options for consumers in terms of product, plans, benefits and period. Life insurance can be separated in two major categories consist conventional insurance and of Islamic insurance which is merely known as Takaful. The main concern is the basis of operation that is different in terms of interpretation and approaches as well as the principles and concepts. A study on the society perceptions between conventional and Islamic life insurance among the community in Jengka Pahang, is the first step in understand mg the society level of understanding and thoughts regarding life insurance. This paper will discuss on the society perceptions between Islamic and conventional insurance and what do they perceived of life insurance. It will also elicits all the factors which contribute to the buying decision of the existing policyholders and what are the factors that preventing society from buying life insurance though the importance is clearly defined.